Evaluation of the “nickel effect” in sulfide stress cracking of low alloy steels - Chalfoun, Dannisa Romina; Kappes, Mariano Alberto; Iannuzzi, Mariano (Pergamon-Elsevier Science Ltd, 2024)
Fil: Chalfoun, Dannisa Romina. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina